The 2008 Battle of Sadr City - Johnson, David E. (RAND Corporation, 2011)
Using primary sources and interviews with those involved in the fighting and its aftermath, the authors describe the 2008 Battle of Sadr City, analyze its outcome, and derive implications for the conduct of land operations. Their analysis identifies factors critical to the coalition victory over Jaish al-Mahdi and describes a new model for dealing with insurgent control of urban areas.